2021
DOI: 10.21037/atm-21-4712
|View full text |Cite
|
Sign up to set email alerts
|

Identification of m6A methyltransferase-related genes predicts prognosis and immune infiltrates in head and neck squamous cell carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) accounts for 90% of head and neck malignant tumors. As the early symptoms of HNSCC are not obvious, and it is prone to recurrence and metastasis, making the overall survival (OS) rate of patients very low. Existing studies have shown m6A methylation plays a crucial role in various cancers, but it is rarely studied in HNSCC. This study aimed to explore the expression of m6A methylation-related genes in HNSCC and its correlation with prognosis, and to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…These therapies have the potential to reduce the burden of disease associated with HPV infection and improve the quality of life of patients [29]. However, the role and mechanism of m6A in the tumor immune response in HPV-associated cancers are not well defined [26,[30][31][32].…”
Section: Ivyspringmentioning
confidence: 99%
“…These therapies have the potential to reduce the burden of disease associated with HPV infection and improve the quality of life of patients [29]. However, the role and mechanism of m6A in the tumor immune response in HPV-associated cancers are not well defined [26,[30][31][32].…”
Section: Ivyspringmentioning
confidence: 99%
“… Cancer type HnRNPs Expression Role Clinical correlation Detection methods Ref. MNs hnRNPA0 Downregulated Anti-cancer Pathologic differentiation Database [ 23 ] MM hnRNPA2/B1 Upregulated Oncogenic OS qRT-PCR [ 86 ] Glioblastoma hnRNPA2/B1 Upregulated Oncogenic Survival Database, qRT-PCR [ 81 ] OSCC hnRNPA1 Upregulated Oncogenic Clinicopathologic stages IHC, western blot [ 47 ] HNSCC hnRNPA2/B1 Upregulated - OS, DSS Database [ 158 ] LC hnRNPA1 Upregulated Oncogenic OS IHC, western blot, qRT-PCR [ 32 , 33 ] hnRNPA2/B1 Upregulated Oncogenic Lung development, early diagnosis, TNM stage, survival Database, IHC, western blot; northern blot [ 75 , 77 , 93 , 159 ] BC hnRNPA2/B1 Conflicting Conflicting Survival IHC, mRNA-sqe, northern blot [ 101 , 106 , 107 , 160 ] ESCA hnRNPA0 Upregulated Oncogenic …”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, HNRNPC has been reported to regulate immunosuppressive events in tumor microenvironment [ 61 , 62 ], and we conducted comparable analyses on HNRNPC to uncover its role in immune systems. Among them, representative methods including ESTIMATE algorithm and ssGSEA were applied to evaluate the immune infiltration level.…”
Section: Discussionmentioning
confidence: 99%